2008
DOI: 10.1148/radiol.2482072192
|View full text |Cite
|
Sign up to set email alerts
|

Prospective versus Retrospective ECG Gating for 64-Detector CT of the Coronary Arteries: Comparison of Image Quality and Patient Radiation Dose

Abstract: Use of 64-detector CT coronary angiography performed with prospective ECG gating has similar subjective image quality scores but 77% lower patient radiation dose when compared with use of retrospective ECG gating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
270
3
14

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(311 citation statements)
references
References 15 publications
24
270
3
14
Order By: Relevance
“…Following these recommendations, Stolzmann et al reported that despite using wider pulsing windows at higher heart rates, the radiation dose of DSCT decreased as the heart rate increased. Additionally, different studies reported radiation doses between 2.1 and 4.2 mSv using prospective triggering [23][24][25]. However this technique is only recommended in patients at lower and stable heart rates and with a fairly low body weight [23,26].…”
Section: Discussionmentioning
confidence: 99%
“…Following these recommendations, Stolzmann et al reported that despite using wider pulsing windows at higher heart rates, the radiation dose of DSCT decreased as the heart rate increased. Additionally, different studies reported radiation doses between 2.1 and 4.2 mSv using prospective triggering [23][24][25]. However this technique is only recommended in patients at lower and stable heart rates and with a fairly low body weight [23,26].…”
Section: Discussionmentioning
confidence: 99%
“…16 In the interest of using an effective dose that is obtained with the latest generally available technology, we assume a 4.2mSv effective dose for prospectively ECG-gated cCTA based upon clinical reports. 17,18 For the purpose of sensitivity analysis, since many centers have not yet adopted prospectively gated cCTA, the effective dose of cCTA was also varied up to 10mSv as demonstrated in a recent multicenter trial using the more conventional helical CTA with tube current modulation. 19 The effective dose for diagnostic cardiac catheterization was set at 7mSv for the base analysis, but was varied down to 5mSv for the sensitivity analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Previous CTCA protocols [2,[16][17][18] did not adapt to patients individual body mass or cardiac output. Consequently, vessel attenuation in CTCA has been shown to vary strongly [6][7][8][9], depending on BMI and to affect the optimal detection of coronary plaque.…”
Section: Introductionmentioning
confidence: 99%